EFFECT OF SAVING AGE FROM SUGARCANE’S WATER STORAGE LIFE TO SWEETENESTLEVEL OF SUGARCANE’ WATER - Destriyani, Leny - (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2014)
Sugarcane is the most important farm commodity in Indonesia. Sugarcane has a short storage life, therefore it takes an alternative storage to extend its storage life that will add value to the sugarcane. The storage of sugarcane by its waterstorage is an alternative option. The purpose of this research is to determine the storage life of sugarcane by its water after harvesting, searching for information on sugar levels forming on the storage of sugarcane by its water, and observe the changes in weight and fhysical sugarcane’s water during retention. This research was configured in two ways, first by sugarcane’s water storage at low temperatures 10 ºC and second by room temperature. From this research, each experiments showed different result. The sugarcane’s storage life old out until 9 days with the experiment using plastic packaging at low temperatue of 10 ºC with the treatment of sugarcane water with the packaging and without plastic packaging. The experiment using room temperature without any plastic packaging last out until 5 days. In each experiments, each showed the increasing in total dissolved solids until the third day, it will decrease everyday, the conclusion is the sugarcane is more efficiently stored on low temperature.Keywords: sugarcane’s water, temperature, packaging, sweetenestLeve, storage life